FRI0216 Results of a longitudinal review of pulmonary function and safety data in a phase iib clinical programme testing granulocyte-macrophage colony-stimulating factor (GM–CSF) receptor antagonist mavrilimumab for treatment of rheumatoid arthritis (RA). (15th June 2017) - Burmester, G; Michaels, MA; Close, D; Godwood, A; Middleton, K; Miranda, P; Vencovský, J; Kremer, J; McInnes, IB; Albulescu^, M; Weinblatt^, M
Abstract : Background: RA is associated with pulmonary comorbidity and lung function decline over time, but longitudinal assessment of pulmonary abnormalities in the context of RA treatment needs further characterisation. Mavrilimumab, an investigational human monoclonal antibody, inhibits GM-CSF by binding to the GM-CSF receptor α subunit. Objectives: To investigate the pulmonary safety of mavrilimumab because of the theoretical risk of inhibiting alveolar macrophage function and causing pulmonary alveolar proteinosis (PAP). Methods: Pulmonary monitoring included standardised serial pulmonary function testing (spirometry and diffusing capacity of lung carbon monoxide [DLCO]), chest X-rays, assessments of dyspnoea and pulmonary adverse events (AEs) in two randomised, double-blind studies (NCT01706926 ; NCT01715896 ) where patients (pts) with moderate to severe RA received mavrilimumab 30, 100 or 150 mg every other week (eow), or placebo and mavrilimumab 100 mg eow or golimumab 50 mg every 4 weeks, respectively. Eligible pts transferred to the open-label extension study (NCT01712399 ) and received mavrilimumab 100 mg eow. All studies excluded pts with clinically significant uncontrolled pulmonary disease. An Independent Pulmonary Evaluation Committee (IPEC), blinded to treatment, adjudicated pulmonary AEs and lung function abnormalities. Results: Mavrilimumab was received by 442 pts with cumulative safety data exposure of approximately 900 pt-yrs and a median (range) exposure time of 2.5 (0.1–3.3) yrs. Baseline (BL) characteristics are shown (Table). Mean dyspnoea (Table), forced expiratory volume in 1 second (FEV1 ), forced vital capacity (FVC) and DLCO were mostly maintained within 5% of BL values for pts treated with mavrilimumab during the clinical programme. Clinically relevant decreases in predicted FEV1 and FVC (>20% from BL and <80% predicted) were demonstrated by ≤6.2% of pts at any visit (Table); decreases were mostly transient with no apparent trends. Overall, 83 pts (9.24/100 pt-yrs) reported ≥1 pulmonary AE; bronchitis was reported most frequently (34 pts [3.78/100 pt-yrs]); one AE was considered serious and treatment-related (acute bronchitis). The reported pulmonary AE rate was generally stable over time. No suspected or confirmed PAP cases were found by IPEC and no pulmonary-related deaths were reported. Conclusions: We believe this is the most comprehensive longitudinal study of pulmonary function in a clinical RA programme. The BL pulmonary function profile indicates that this is not a normal population from a pulmonary health perspective. Mavrilimumab was not associated with substantial decline in pulmonary function or PAP in pts treated up to 3.3 years; its acceptable safety profile advocates initiation of Phase III studies with mavrilimumab. Further studies are now required to fully characterise pulmonary function over time in RA. Acknowledgements: Funded by MedImmune. Medical writing support: R Plant, QXV Comms, an Ashfield company, funded by MedImmune. ^Senior author. Disclosure of Interest: G. Burmester Consultant for: MedImmune, M. Michaels Employee of: MedImmune, D. Close Employee of: MedImmune, A. Godwood Shareholder of: AstraZeneca, Employee of: MedImmune, K. Middleton Employee of: MedImmune (contracted employment at time of study), P. Miranda Grant/research support from: Amgen, Medimmune, Janssen, Pfizer, Celltrion, Abbott, Sanofi, Actelion, Merck & Co, Boehringer, BMS, Consultant for: Pfizer [Etanecept: Fee less than USD5000], J. Vencovský Consultant for: Pfizer, Elli Lilly, MSD, Novartis, Speakers bureau: Biogen, Pfizer, MSD, Abbvie, Novartis, Boehringer, UCB, BMS, J. Kremer Shareholder of: Corrona, Grant/research support from: Abbvie, Amgen, Genentech, Lilly, Pfizer, Consultant for: Abbvie, Amgen, BMS, Genentech, Lilly, Pfizer, Employee of: Corrona, I. McInnes Grant/research support from: MedImmune [The University of Glasgow is a charity registered in Scotland, charity number SC004401 Grant/research support: Research award to University of Glasgow], Consultant for: MedImmune, M. Albulescu Shareholder of: MedImmune, Employee of: MedImmune, M. Weinblatt Grant/research support from: BMS, UCB, Crescendo Bioscience. Amgen, dxterity, Consultant for: MedImmune, Astra Zeneca, Amgen, Abbvie, BMS, Crescendo bioscience, Lilly, Pfizer, UCB, Roche, novartis